Biotechnological Applications of Fertile, Transgenic Oat Plant - Ms. Subhasmita Rout, S. Gopa Mishra, Prof. Alok Nandi (International Journal of Modern Agriculture, 2020)
The resistance of Oat (Avena sativa L.) is low due to drought and salinity in the world’s temperate cereal crop. A genotype-independent and efficient regeneration system using four oat cultivars, Prairie, Porter, Ogle and Pacer, was developed for genetically transforming the commercial oat cultivar available in this field. All these oat varieties produced multiple shoots from apical shoot meristems at a high frequency in vitro-independent genotype. This method was used to co-genetically transform three oat cultivars using biolistic TM bombardment with pBY520 (hva1 and bar) and pAct1-D (gus-containing). Herbicide tolerance and GUS markers have been used to identify and regenerate transgenic plants. The co-integration of hva1 and bar genes, at 100% and 61.6 percent of transgenic plants carried all three genes (hva1, bar and gus), is supported by molecular and biochemical analysis of putative transgenic plants. Further analysis of progeny R0, R1 and R2 verified that all of the transgenes are stable integration, expression and Mendelian heritage. A high GUS level of expression in vascular tissues and in the pollen grain of mature flowers has been shown in histo-chemical analysis of GUS protein in transgenic plants. In all stages of development, the immunochemical analysis of transgenic plants showed that hva1 was constitutive expression. In the early planting stages, however, HVA1 was higher.